Hidden in Plain Sight: Detecting Invasive Species When They Are Morphologically Similar to Native Species - Fisher, Samuel; Fisher, Robert N.; Pauly, Gregory B. (Frontiers in Conservation Science, 2022)
Early detection and rapid response (EDRR) can help mitigate and control invasive species outbreaks early on but its success is dependent on accurate identification of invasive species. We evaluated a novel outbreak in San Diego County, California of the Sonoran Spotted Whiptail (Aspidoscelis sonorae) in order to confirm their spread as well as quantify how to better detect and potentially manage this invasive species in California. We found that A. sonorae went undetected for over two years due to its morphological similarity to native whiptails and that it has spread rapidly since they were first observed. There are two species of native California whiptails with which A. sonorae can be confused locally, the Orange-throated Whiptail (Aspidoscelis hyperythrus), and to a lesser extent the Tiger Whiptail (Aspidoscelis tigris). We review key diagnostic features to distinguish A. sonorae from native California whiptails. We also discuss how to efficiently use widely available community science tools to rapidly assess a novel invasive species outbreak and outline suggestions to help manage cryptic invasive species.